Radioresistance in rectal cancer: can nanoparticles turn the tide? - Diogo Coelho; Diogo Estêvão; Maria José Oliveira; Bruno Sarmento (Molecular Cancer)
Abstract Rectal cancer accounts for over 35% of the worldwide colorectal cancer burden representing a distinctive subset of cancers from those arising in the colon. Colorectal cancers exhibit a continuum of traits that differ with their location in the large intestine. Due to anatomical and molecular differences, rectal cancer is treated differently from colon cancer, with neoadjuvant chemoradiotherapy playing a pivotal role in the control of the locally advanced disease. However, radioresistance remains a major obstacle often correlated with poor prognosis. Multifunctional nanomedicines offer a promising approach to improve radiotherapy response rates, as well as to increase the intratumoral concentration of chemotherapeutic agents, such as 5-Fluorouracil. Here, we revise the main molecular differences between rectal and colon tumors, exploring the complex orchestration beyond rectal cancer radioresistance and the most promising nanomedicines reported in the literature to improve neoadjuvant therapy response rates. Graphical Abstract